Presence of adropin, nesfatin-1, apelin-12, ghrelins and salusins peptides in the milk, cheese whey and plasma of dairy cows - Aydin, Suleyman (Elsevier Science Inc, 2013)
Biological fluids (milk and serum/plasma) and cheese whey milk-derived fluid contain numerous molecules, especially amino acids and proteins. Therefore, the purpose of this study was to find out whether cheese whey (n:6), cow milk (n:6) and its blood (n = 6) have adropin, nesfatin-1, apelin-12, ghrelins and salusin peptides. Adropin, nesfatin-1, apelin-12 concentrations were measured by ELISA, whereas ghrelin and salusin concentrations were measured by EIA methods. It was found that adropin, nesfatin-1, apelin-12, des-acylated ghrelin and salusins in cheese whey were higher than in the corresponding milk peptides and plasma of dairy cows, with the exception of salusin alpha and acylated ghrelin in milk being the same than that of the corresponding cheese whey concentration and plasma of dairy cows. A correlation was also found between milk peptides and cheese whey, as also with plasma of dairy cows. The data suggest that peptides in cow milk might be an important and nutritious food for (neonatal) calves and human diet due to their biological and physiological properties. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Cheese whey; Adropin; Apelin-12; Ghrelins; Nesfatin-1; Salusins